2019
DOI: 10.18769/ijasos.592126
|View full text |Cite
|
Sign up to set email alerts
|

Study on Evaluation of Startup Business Training Models in the Entrepreneurship Skills Education Program at West Java Course and Training Institute, Indonesia

Abstract: The Entrepreneurship Skills Education Program (ESE) has been held since 2016 in Indonesia. The focus of this training is the change in knowledge, skills and attitudes of entrepreneurs with the main target of people who are weak in the economic and educational side. This program is an effort to expand access to education and employment opportunities through the creation of new entrepreneurs. The Course and Training Institute (CTI) has a role in organizing the ESE program. Considering its strategic position in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A research on University Entrepreneurial Ecosystem (UEE) in Russian universities concluded that a perfect balance of both practical and theoretical courses was necessary to build the entrepreneurship skills of students to develop their own startups (Zotov et al, 2019). Similar research studies that assert this view include—Schultz (2021), Soesanto et al (2021), and Saripah et al (2019). The approach that will be adopted by this study is to check the impact of both theoretical and practical entrepreneurship courses—individually—with other factors to determine their importance in a complex relationship.…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…A research on University Entrepreneurial Ecosystem (UEE) in Russian universities concluded that a perfect balance of both practical and theoretical courses was necessary to build the entrepreneurship skills of students to develop their own startups (Zotov et al, 2019). Similar research studies that assert this view include—Schultz (2021), Soesanto et al (2021), and Saripah et al (2019). The approach that will be adopted by this study is to check the impact of both theoretical and practical entrepreneurship courses—individually—with other factors to determine their importance in a complex relationship.…”
Section: Theoretical Backgroundmentioning
confidence: 79%
“…The research uses a qualitative method, which has the goal of uncovering and building a proportion or explaining the meaning behind a reality. As explained [100,101], a qualitative descriptive method is defined as a procedure for solving the problem investigated, by describing the circumstances of the object of the research at the present time, based on the facts that appear or as they really are. The basis of the approach used in community development must be community characteristics [102].…”
Section: Methodsmentioning
confidence: 99%